ANTROPOLOŠKO-ETIČNI TEMELJI ČLOVEŠKE KULTURE (Филолошки студии, 2019)
From old times the religion, philosophy and arts make the grounds of the man’s culture. The man found in them his anthropological and ethical origins and his centre. A characteristic of the classical cultures was to preserve the originality and the profoundness of life. The development of the culture of New Ages made these grounds outer and total. Many (post)modern thinkers pay attention to these problems. After all experiences with the modern totalitarian regimes, it is becoming more and more urgent to find these cultural origins again. The subtle dialog of culture should be cultivated. All areas of culture must be involved, not only religion, philosophy, arts and sciences, but also the politics, economy, all branches of production. Whether the man is prepared to find out and to implement the mechanisms of the long duration, demanded by the logic of the Christ’s Sermon on the mount (Lc 5, 1-12), that is the problem of his survival.